The Influence of Financial Literacy, Digital Innovation, and Entrepreneurial Orientation on the Performance of MSMEs in the Post-Pandemic Era in Indonesia - Israel Olukayode ADEBOWALE; Sukarta Atmaja; Ria Puspitasari; Dewi Amalia; Annuridya Rosyidta Pratiwi Octasylva (Westscience Press, 2026)
The post-pandemic era has brought significant challenges and opportunities for micro, small, and medium enterprises (MSMEs) in Indonesia, particularly in terms of financial management, digital adaptation, and strategic orientation. This study examines the influence of financial literacy, digital innovation, and entrepreneurial orientation on MSME performance in the post-pandemic context. A quantitative research approach was employed, with data collected from 135 MSME owners and managers using a structured questionnaire measured on a Likert scale. The data were analyzed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS) version 25. The results indicate that financial literacy has a positive and significant effect on MSME performance, demonstrating the importance of sound financial knowledge and management skills in supporting business recovery. Digital innovation is found to have the strongest positive influence on performance, highlighting the critical role of digital technology adoption in enhancing competitiveness and market reach. Entrepreneurial orientation also shows a significant positive effect, emphasizing the importance of innovativeness, proactiveness, and risk-taking in navigating post-pandemic uncertainty. Simultaneously, financial literacy, digital innovation, and entrepreneurial orientation significantly explain variations in MSME performance. These findings suggest that strengthening internal capabilities through integrated financial education, digital capacity building, and entrepreneurship development is essential for improving MSME resilience and sustainable growth in Indonesia’s post-pandemic economy.